# Verification of this summation [closed]

How do I check or evaluate this summation

$$\sum_{k\ge 0} \left(\frac12\right)^{k+1}k=1$$

-

## closed as off-topic by ᴡᴏʀᴅs, heropup, Eric Stucky, Brian Fitzpatrick, qwrJun 10 '14 at 6:37

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – ᴡᴏʀᴅs, heropup, Eric Stucky, Brian Fitzpatrick, qwr
If this question can be reworded to fit the rules in the help center, please edit the question.

Hint

Consider $$\sum_{k=0}^\infty x^{k+1}k=x^2\sum_{k=0}^\infty x^{k-1}k=x^2 \frac{d}{dx}\Big(\sum_{k=0}^\infty x^k\Big)=x^2\frac{d}{dx}\Big(\frac{1}{1-x}\Big)=\frac{x^2}{(1-x)^2}$$ Now replace $x$ by $\frac{1}{2}$ and you are done

-

Multiply by $2$. Note that the first term is $0$, so we want to show that $$\sum_1^\infty k\left(\frac{1}{2}\right)^k=2.\tag{1}$$

Define random variable $X$ as follows. Imagine tossing a fair coin until we get a head. Let $X$ be the number of tosses. Then for $k\ge 1$ we have $\Pr(X=k)=\frac{1}{2^k}$. It follows that the sum (1) is $E(X)$.

Let $e$ be the expectation of $X$. Condition on the first toss. If the first toss is a head, then $X=1$, so the conditional expectation of $X$, given that we get a head on the first toss, is $1$.

If the first toss is a tail, then we have used up one toss, and the expected number of additional tosses until we get a head is $e$. It follows that $$e=\frac{1}{2}\cdot 1+\frac{1}{2}\cdot(1+e).$$ Solve this linear equation for $e$. We get $e=2$.

-

For $|x| < 1$ we have: $\displaystyle \sum_{k=0}^\infty kx^{k-1} = \left(\dfrac{1}{1-x}\right)' = \dfrac{1}{(x-1)^2}$. Thus: $\displaystyle \sum_{k=0}^\infty kx^{k+1} = \dfrac{x^2}{(x-1)^2}$. Put $x = 1/2$ in the equation to get the answer: $1$

-

hints:

$$|x|<1\implies\frac1{1-x}=\sum_{n=0}^\infty x^n\implies\frac1{(1-x)^2}=\sum_{n=1}^\infty nx^{n-1}$$

What then happens with $\;x=\frac12\;$ and...?

-